Possible molecular mechanisms of persistent pollen tube growth without de novo transcription - Motomura, Kazuki; Sugi, Naoya; Takeda, Atsushi; Yamaoka, Shohei; Maruyama, Daisuke (Frontiers in Plant Science, 2022)
The vegetative cell nucleus proceeds ahead of a pair of sperm cells located beneath the pollen tube tip during germination. The tip-localized vegetative nucleus had been considered to play a pivotal role in the control of directional pollen tube growth and double fertilization. However, we recently reported the female-targeting behavior of pollen tubes from mutant plants, of which the vegetative nucleus and sperm nuclei were artificially immotile. We showed that the apical region of the mutant pollen tubes became physiologically enucleated after the first callose plug formation, indicating the autonomously growing nature of pollen tubes without the vegetative nucleus and sperm cells. Thus, in this study, we further analyzed another Arabidopsis thaliana mutant producing physiologically enucleated pollen tubes and discussed the mechanism by which a pollen tube can grow without de novo transcription from the vegetative nucleus. We propose several possible molecular mechanisms for persistent pollen tube growth, such as the contribution of transcripts before and immediately after germination and the use of persistent transcripts, which may be important for a competitive race among pollen tubes.